RELEVANCE OF INTEGRATION OF AYURVEDA AND MODERN 4-P MEDICINE IN PREVENTION OF NON-COMMUNICABLE DISEASES - O, *Safonicheva; Dilipkumar, K.V. (International Journal of Ayurveda and Pharma Research, 2016)
Statistics shows that the current measures for controlling non-communicable diseases are not adequate. This signifies the need of emergence of new concepts in health care system. In contrast to the infectious diseases, non-communicable diseases necessitate early diagnosis and personalized prevention. In tune with the new world trends Russian government approved the strategy of development of the technological platform "preventive environment". Platform is an integrated program of research in priority areas of health research, aimed at creating innovative products and technologies of personalized medicine.In the current scenario the concepts of modern 4-P medicine become more relevant. 4-P medicine is integrating with worlds best schools of medicine to broaden its understanding of personalized approach. This article highlights the need of integration of 4-P medicine and Ayurveda. To a greater extend the concepts of Ayurveda-ancient Indian system of medicine corresponds ideologically with 4-P medicine. Therefore an integrated effort in this direction will be of great help in prevention and cure of non-communicable diseases. Integrated approach of 4-P medicine and Ayurveda can play a major role in the strategy development of preventive environment.